Surgical management outcomes of recurrent thyroglossal duct cyst in children – A systematic review. Issue 6 (June 2015) - Ibrahim, Farid F.; Alnoury, Mohammed K.; Varma, Namrata; Daniel, Sam J.
Abstract: Objectives: Management of recurrent thyroglossal duct cysts (TGDC) remains a clinical challenge to otolaryngologists – head and neck surgeons. The purpose of this systematic review is to determine the best surgical management for recurrent TGDC. Methods: A comprehensive search for relevant articles was carried out on electronic databases named Ovid Medline, Ovid Medline in process and Other Non-Indexed Citations, Embase, Ovid OldMedline, and Ovid Medline Daily. Articles published in English until 2014 were eligible for review. Using predefined inclusion criteria, published articles on surgical outcomes in the management of recurrent thyroglossal duct cyst, were selected, reviewed, and their findings synthesized. Results: Nine studies met the inclusion criteria for this systematic review comprising a total of 66 patients who underwent 114 secondary surgeries. Better outcomes were observed with en bloc neck dissection vs. a revision Sistrunk with a recurrence rate of 20% vs. 30.12% respectively. In addition two new surgical approaches, suture-guided transhyoid pharyngotomy and Koempel's suprahyoid technique reported 100% success rate. Conclusion: Recurrence after primary surgical management remains a clinical challenge. We highlight the outcomes of the 4 main surgical techniques reported in the literature, repeat Sistrunk procedure, en bloc neck dissection, suture-guided transhyoid pharyngotomy, and Koempel's suprahyoid technique. Although this review reports a 100% success rate with the 2 latter techniques, further prospective studies and additional experience with these same techniques by other surgeons/institutions with or without a randomized trial could provide additional confirmation of improved outcomes using these specific surgical procedures.